Redressal of Consumer Grievances: A Case Study of State Consumer Disputes Redressal Commission, Chandigarh - Sukhdeep,; Gill , Rajbans Singh (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
Our society has, essentially, been dynamic though its speed of dynamism is found to be varying between that of the bullock-carts to that of the space travel. Man, being a social and rational animal has ever tried to improve upon everything he laid hands on or anything he had invented or discovered.1 His special faculty to thoughtfulness has always been inspiring to channelize all his energies to reach a destination of perfection in life. The inherent virtues of interaction and interdependence of the human beings2 are taken to be the symbol of dynamism of a civilization. The existing commercialization of every sphere of life gives much more prominence to the most subtle and indispensable interaction between the trader and the consumer. Consumer is all of us and all of us are consumers. Guided, instinctively, by the stomach,3 we are first the consumers and later the producers. And consumers we remain forever, not merely from cradle to grave, but even beyond these two extremes of our physical existence while producers we remain for a comparatively shorter period of our full life cycle. The simplest sharing of one’s surplus produce in1 Anoop K. Kaushal, (2005), Medical Negligence and Legal Remedies, Universal Law Publishing Co. Pvt. Ltd., Delhi, pp. 2-3. 2 Justice Rama Jois, (2000), Seeds of Modern Public Laws in Ancient Indian Jurisprudence and Human Right, Bhartiya Values, Lucknow, p. 1. 3 A very nice Conclusion of Swami Vivekanand Ji.exchange for the reciprocated surpluses of different commodities of use, produced by others, was the origin proper of the Barter trade which is as old the society itself.4